Development Web-Based Learning Web on Acids and Bases - RD, Qomaruddin; Sitorus, Marham; Dibyantini , Ratu Evina (Education, Science, and Technology International Conference, 2024)
Basically, the benefits of technology-based learning in supporting the implementation of the learning process can increase students' absorption capacity in understanding the context of learning material, encourage independent learning abilities, teachers must be able to use the learning web by using existing technology which makes it easier for students to learn from observations that have been made. In high school chemistry learning currently only uses textbooks and the web, and gives assignments so that it makes learning less interesting for students and sometimes makes students understand less of the content of the learning material. The aim of this research is to develop a web-based learning website that is developed in chemistry lessons, and the feasibility of the web-based learning website being developed. This Google Sites web-based learning research and development model uses the ADDIE learning model. This research uses a non-test instrument in the form of a validation sheet. The validation feasibility results show that the web learning web development on acid and base material, the assessments of material expert validators, web experts and chemistry teachers, for the feasibility of the web development respectively are 83.5%; 86%; 86%; which means that the web-based learning website on Acids and Bases material is very suitable for use as a learning website.